Battery diaphragm and preparation method thereof, secondary battery and electric device
By applying natural latex and ceramic powder coatings on the lithium-ion battery separator, the battery safety risk caused by insufficient ductility of the separator is solved, and higher heat resistance and safety are achieved.
Patent Information
- Application Number
- CN202411807651.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
AI Technical Summary
The insufficient ductility of existing lithium-ion battery separators can easily lead to battery safety risks, especially when they encounter punctures of sharp objects, they are prone to fire or explosion.
A battery separator is used, which includes a base film and a coating. The coating consists of natural latex and ceramic powder. Natural latex accounts for 40 to 80%. Ceramic powder includes aluminum oxide, nanosilicon dioxide and boehmite, etc. The average particle size of ceramic powder is 0.1 to 1 micron.
By improving the heat resistance and ductility of the diaphragm, the safety risks caused by overheating or short circuit are reduced, and the safety and mechanical properties of the battery are enhanced, and the puncture resistance is resisted.
Smart Images

Figure CN119674426A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a battery separator and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] The electrode potential of metallic lithium is very low, which makes lithium-ion batteries have a very high voltage. Since its discovery in the 1990s, lithium-ion batteries have made great progress and are widely used in various fields, such as: mobile phones, mobile power supplies, electric vehicles, UPS, energy storage power stations, etc. Lithium-ion batteries have a variety of positive electrode material systems, such as: lithium cobalt oxide, ternary materials, lithium iron phosphate, lithium manganese oxide, lithium iron manganese phosphate, etc. The negative electrode material is mainly graphite material, including artificial graphite and natural graphite. Sometimes some silicon oxide-based materials are doped in the graphite to further increase the energy density of the battery. Sodium-ion batteries have a similar mechanism to lithium-ion batteries, and sodium ions are very abundant in nature, unlike lithium ions, which are very low in abundance on the earth and unevenly distributed, so sodium-ion batteries have also made great progress in recent years.
[0003] Generally, batteries that use organic solvents as electrolyte solvents have some disadvantages. For example, due to their high voltage, the dust between the positive and negative electrodes can easily lead to large self-discharge of the battery. The large differences between batteries can lead to a lower battery assembly rate and a lower pass rate. At the same time, it also has another natural disadvantage, that is, organic solvents are very easy to burn. When the battery fails or encounters external damage, the battery is very easy to burn and there is a possibility of explosion. In particular, due to the poor heat resistance and ductility of the diaphragm, when a sharp object pierces the battery, the positive and negative pole pieces are instantly short-circuited, and it is very easy to cause a fire or even an explosion. In order to solve this problem, a layer of ceramic slurry is coated on the surface of the diaphragm, which enhances the high temperature resistance and puncture resistance of the diaphragm to a certain extent, and improves the safety of the battery, but it cannot completely avoid the occurrence of battery safety accidents.
[0004] Therefore, there is an urgent need for a lithium-ion battery separator with better ductility and safety. Summary of the invention
[0005] The main purpose of this application is to propose a battery separator and its preparation method, a secondary battery and an electrical device, aiming to provide a solution to the current problem that the separator has poor ductility and is prone to battery safety risks.
[0006] The present application provides a battery separator, the battery separator comprising:
[0007] basement membrane; and
[0008] The coating is at least arranged on one side of the base film, and the material of the coating includes a binder and an insulating material, wherein the binder is natural latex, and the natural latex accounts for 40-80% of the material of the coating.
[0009] In some embodiments, the insulating material comprises ceramic powder, the ceramic powder comprises at least one of alumina, nano-silicon dioxide and boehmite; and / or,
[0010] The material of the base film includes at least one of polyolefin, polyester and polyurethane.
[0011] In some embodiments, the insulating material includes ceramic powder, and the average particle size of the ceramic powder is 0.1 to 1 micrometer.
[0012] In some embodiments, the solid content of the natural latex is 10%-80%.
[0013] The present invention provides a method for preparing a battery separator, comprising the following steps:
[0014] Mixing the binder with the insulating material to form a coating slurry;
[0015] The coating slurry is coated on a base film and cured to prepare a battery separator.
[0016] In some embodiments, the coating slurry has a solid content of 40-50%.
[0017] In some embodiments, in the step of coating the coating slurry onto a base film and curing to prepare a battery separator, the coating thickness is 2 to 5 μm.
[0018] In some embodiments, the steps of applying the coating slurry to a base film and curing the base film to obtain a battery separator include:
[0019] The base film coated with the coating slurry is placed at a temperature of 40 to 45° C. and dried for 25 to 30 seconds.
[0020] The present invention provides a secondary battery, which includes the battery separator in the above embodiment or the battery separator prepared in the above embodiment.
[0021] The present invention further provides an electric device, which includes the secondary battery in the above embodiment.
[0022] In the technical solution of the present invention, the insulating material in the coating of the present invention is coated on the surface of the diaphragm, mainly to improve the heat resistance and safety of the diaphragm, prevent the diaphragm from melting or rupturing when the battery is overheated or short-circuited, and then cause positive and negative short circuits and thermal runaway. At the same time, natural latex is added as a binder to ensure that the ceramic coating can be evenly attached to the surface of the battery diaphragm. Since rubber has ultra-high ductility, the ductility of the battery diaphragm coating is improved, which is conducive to greatly reducing the damage and losses caused by serious accidents. In the material of the coating, the natural latex accounts for 40 to 80% of the material of the coating. The reasonable ratio of ceramic powder and binder within this range can ensure that the ceramic particles are evenly distributed, so that the coating has excellent high temperature resistance, and can also improve the mechanical properties and puncture resistance of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 This is a schematic diagram of the preparation process of battery separators in some embodiments of the present application.
[0025] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0026] It should be noted that, in the embodiments, those without specifying specific conditions are carried out according to normal conditions or conditions recommended by the manufacturer. Those without specifying the manufacturer of reagents or instruments used are conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, and "A and / or B" is taken as an example, including schemes A, B, or A and B that meet the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of the technical schemes is contradictory or cannot be achieved, it should be considered that the combination of such technical schemes does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work, all belong to the scope of protection of the present invention.
[0027] Generally, batteries that use organic solvents as electrolyte solvents have some disadvantages. For example, due to their high voltage, the dust between the positive and negative electrodes can easily lead to large self-discharge of the battery. The large differences between batteries can lead to reduced battery assembly rate and lower qualified rate. At the same time, it also has another natural disadvantage, that is, organic solvents are very easy to burn. When the battery fails or encounters external damage, the battery is very easy to burn and there is a possibility of explosion. In particular, when a sharp object pierces the battery, the positive and negative poles are instantly short-circuited, which is very likely to cause fire or even explosion. In order to solve this problem, a layer of ceramic slurry is coated on the surface of the diaphragm, which enhances the safety of the battery to a certain extent, but it cannot completely avoid the occurrence of battery safety accidents.
[0028] Therefore, there is an urgent need for a lithium-ion battery separator with better ductility and safety.
[0029] In view of this, the present invention provides a battery separator, which includes a base film and a coating, wherein the coating is provided on at least one side surface of the base film, and the material of the coating includes a binder and an insulating material, wherein the binder is natural latex, and the natural latex accounts for 40 to 80% of the material of the coating.
[0030] It should be noted that natural latex is a milky liquid extracted from the bark of the rubber tree (Hevea brasiliensis), and its main component is a colloidal liquid in which rubber particles are suspended in water. It is a natural polymer, mainly composed of cis-1,4-polyisoprene, and has good elasticity, softness and durability. Natural latex is often used to produce various rubber products, such as latex gloves, latex pillows, balloons, tires, etc., and the coating is at least provided on one side of the base film, and the coating can also be applied to the surfaces of both sides of the base film.
[0031] In the technical solution of the embodiment of the present application, the insulating material in the coating of the present invention is coated on the surface of the diaphragm, mainly to improve the heat resistance and safety of the diaphragm, prevent the diaphragm from melting or rupturing when the battery is overheated or short-circuited, and then cause positive and negative pole short circuit and thermal runaway. At the same time, natural latex is added as a binder to ensure that the coating of the insulating material can be evenly adhered to the surface of the battery diaphragm. Since rubber has ultra-high ductility, it is beneficial to minimize the damage and losses caused by serious accidents. In the material of the coating, the natural latex accounts for 40 to 80% of the material of the coating. The reasonable ratio of insulating material and binder within this range can ensure that the insulating material is evenly distributed, so that the coating has excellent high temperature resistance, and can also improve the mechanical properties and puncture resistance of the diaphragm.
[0032] In some embodiments of the present application, the ceramic powder includes at least one of alumina, nano-silica and boehmite. It can be understood that the insulating material can be alumina or boehmite, or nano-silica and boehmite. In the embodiments here, the ceramic powder preferably is alumina, which has high temperature stability to prevent the diaphragm from shrinking or melting in a high temperature environment, as well as electrical insulation and puncture resistance, thereby improving the safety of lithium-ion batteries.
[0033] The material of the base film includes at least one of polyolefin, polyester and polyurethane, and can be any one of the above substances, or a combination of any two or more thereof. Polyolefin is preferably used as the base film, which facilitates the passage of lithium ions and acts as a physical isolation layer to prevent short circuit between the positive and negative electrodes.
[0034] The insulating material includes ceramic powder, and the average particle size of the ceramic powder is 0.1 to 1 micron. Within the above range, the ceramic powder can be mixed evenly when it is subsequently prepared into a coating slurry.
[0035] Furthermore, in some embodiments, the solid content of the natural latex is 10%-80%.
[0036] It is understood that the solid content of natural latex refers to the percentage of rubber particles in natural latex, usually expressed as a percentage. It measures the proportion of rubber solids in the latex liquid and determines the concentration of the latex. For example, if the solid content of natural latex is 60%, it means that 60% of the latex liquid is rubber solids, and the remaining 40% is water and other components. In addition to rubber solids, natural latex liquid also contains water, proteins, lipids, resins and sugars. The concentration of latex can be increased by increasing the solid content. And the solid content of natural latex directly affects its elasticity, hardness, drying time and service life. The higher the solid content, the stronger and more durable the product is, and the better the elasticity is; when the solid content is lower, the product will be softer, more breathable, and the drying time will be longer. According to different application requirements, the solid content of latex will be adjusted accordingly to optimize performance. In some embodiments of the present invention, the solid content of the natural latex is 10%-80%, so that the ductility of the battery separator coating obtained is better.
[0037] The present invention provides a method for preparing a battery separator, such as Figure 1 As shown, the following steps are included:
[0038] S10, mixing the binder and the insulating material to prepare a coating slurry;
[0039] S20, coating the coating slurry onto a base film, and curing the coating slurry to obtain a battery separator.
[0040] In the technical solution of the embodiment of the present application, the adhesive is mixed with the insulating layer material, dispersed evenly to obtain a coating slurry, and then the coating slurry is cured and evenly coated on the base film, which helps to ensure the safety of the diaphragm.
[0041] It can be understood that the proportion of solid components in the coating slurry, that is, the proportion of solid components such as ceramic powder and natural latex, directly affects the mechanical properties and ductility of the coating. When the proportion of ceramic powder is high, there are more rigid particles in the coating, and the latex component is difficult to form a tough network, which will reduce the flexibility of the coating and make it more likely to break or lose its deformation ability when subjected to mechanical stress (such as bending or stretching). However, the mechanical strength and thermal stability will be improved. Therefore, a suitable solid component ratio can not only ensure the ductility of the diaphragm coating, but also take into account the mechanical properties and thermal stability. In some embodiments, the solid content of the coating slurry is 40-50% for best results.
[0042] In some embodiments, in the step of coating the coating slurry onto a base film and curing to prepare a battery separator, the coating thickness is 2 to 5 μm.
[0043] The coating thickness of the coating slurry is too high. A thicker coating increases the stiffness of the material, but it is also more likely to break when subjected to force. A lower thickness will weaken the puncture resistance and high temperature resistance of the diaphragm and increase the risk of battery short circuit. Therefore, in some embodiments, it is better to set the coating thickness to 2 to 5 μm.
[0044] In some embodiments, the steps of applying the coating slurry to a base film and curing the base film to obtain a battery separator include:
[0045] The base film coated with the coating slurry is placed at a temperature of 40 to 45° C. and dried for 25 to 30 seconds.
[0046] In the technical solution of the embodiment of the present application, the coating slurry is solidified and formed into a coating. Under this temperature condition, the coating slurry is well combined with the base film and the curing efficiency is high.
[0047] The present invention provides a secondary battery, which includes the battery separator in the above embodiment or the battery separator prepared in the above embodiment. The secondary battery includes the battery separator as in the above embodiment, and also includes a positive electrode plate, a negative electrode plate and an electrolyte.
[0048] The present invention further provides an electric device, which includes the secondary battery in the above embodiment.
[0049] The electrical devices proposed in this application include but are not limited to: mobile phones, laptop computers, electric vehicles, spacecraft, etc. The electrical devices proposed in this application have all the beneficial effects of the above-mentioned battery separators, which will not be described one by one here.
[0050] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0051] Experimental Materials
[0052] Ceramic powder was purchased from Jiangsu Xinke Zhonglian New Materials (Changzhou) Co., Ltd., model XKM219;
[0053] Natural latex was purchased from Jingbang New Composite Materials Co., Ltd., model number XY-8625HB.
[0054] Example 1
[0055] The battery separator includes a polypropylene base film and a coating disposed on one side of the base film, the thickness of the coating is 3 μm, the material of the coating includes an insulating material (ceramic powder) and a binder (natural latex, the solid content of which is 40%), and the natural latex accounts for 40% of the material of the coating;
[0056] The preparation method of the battery separator includes:
[0057] (1) Mixing a binder with an insulating material to prepare a coating slurry;
[0058] (2) The coating slurry is applied to a base film, dried at 60° C. for 120 seconds, and cured to obtain a battery separator. The solid content of the coating slurry is 45%.
[0059] Except for the content of ceramic powder, the solid content of natural latex and the solid content of coating slurry, Examples 2 to 15 are the same as Example 1, as shown in Table 1:
[0060] Table 1 Component ratio of each embodiment
[0061]
[0062] Comparative Example 3
[0063] The natural latex in Example 1 was replaced with commercially available synthetic latex, wherein the synthetic latex was PAA glue solution purchased from Chengdu Yindi Le Company with a brand number of LA133.
[0064] Performance Testing
[0065] The battery separators prepared in each embodiment and the battery separators provided in the comparative examples were subjected to relevant performance tests, and the test methods and results are as follows:
[0066] Use a 0.5mm diameter steel needle to perform a puncture test at a vertical angle to the diaphragm surface at a speed of 0.5mm per second to observe the performance of the diaphragm after being punctured, including:
[0067] A: The diaphragm substrate is pierced while the coating layer is not pierced and is wrapped around the steel needle
[0068] B: The membrane substrate is pierced while the coating layer is also pierced;
[0069] Put the coated surface and the uncoated surface of the diaphragm together, apply a force of 1 Newton / square centimeter, and then check whether they are adhered together;
[0070] The separator is wound into a cylindrical battery and the battery is subjected to a needle penetration test to detect whether the rate of thermal runaway of the battery is reduced.
[0071] The method of battery manufacturing is as follows:
[0072] The ternary material, conductive carbon nanotubes, PVDF, and NMP are prepared in a ratio of 97.5:1:1.5:45, PVDF is dissolved in NMP solvent to obtain a clear solution, and then the conductive carbon nanotubes are added to the solution and dispersed evenly, and finally the ternary material is added and dispersed evenly, and then the slurry is coated on aluminum foil, dried, rolled, slit, and the tabs are welded to obtain a positive electrode sheet;
[0073] Graphite, conductive carbon black, CMC, SBR, and water are prepared in a ratio of 96:1:1.3:1.7:130, CMC is dissolved in water to obtain a clear solution, and then conductive carbon black is added to the solution and dispersed evenly, graphite is added and dispersed evenly, and then SBR is added and stirred evenly, and the obtained slurry is coated on a copper foil, and then dried, rolled, slit, and the tabs are welded to obtain a negative electrode sheet;
[0074] The positive electrode sheet, separator, negative electrode sheet and separator are stacked together and wound to form a core, which is then placed in a shell. The bottom negative electrode is welded, and the top cap is welded after rolling the groove. After vacuum drying, the electrolyte is injected and sealed to complete the battery cell. After aging, formation and capacity separation, a qualified battery is obtained. The test results are shown in Table 2.
[0075] Table 2 Test results of battery separators of examples and comparative examples
[0076]
[0077]
[0078] The “ / ” indicates that the battery manufacturing process is not feasible due to the adhesion of the separator.
[0079] According to the test results in Table 1, compared with Comparative Examples 1, 2 and 3, the coatings of Examples 1 to 13 have better ductility, because the ductility of the coatings increases as the rubber content increases. However, rubber has a strong adhesive force, and the diaphragm coated on one side will adhere to the other uncoated side when rolled. Examples 1 to 3 and 5 to 9 have good ductility and are not easy to adhere to the other uncoated side, which is better. Examples 4 to 5 and 10 to 13 have good ductility and are easy to adhere to the uncoated diaphragm surface, which is worse. Comparative Example 3 has too poor ductility in its coating, and does not have the performance of improving the safety of acupuncture.
[0080] The overall solid content of the ceramic slurry has little effect on the properties of the coating and only affects the coating and drying processes.
[0081] At the same time, the prepared separator was used to prepare a cylindrical 18650 battery with a capacity of 2500mAh, and a needle penetration test was performed on the cylindrical battery. This is because the high content of natural latex is beneficial to delaying the reaction time of thermal runaway of the battery.
[0082] The above are only preferred embodiments of the present application, and do not limit the scope of the present application. For those skilled in the art, the present application may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of the patent protection of the present application.
Claims
1. A battery separator, characterized in that: The battery separator comprises: basement membrane; and The coating is at least arranged on one side of the base film, and the material of the coating includes a binder and an insulating material, wherein the binder is natural latex, and the natural latex accounts for 40-80% of the material of the coating.
2. The battery separator according to claim 1, characterized in that The insulating material comprises ceramic powder, and the ceramic powder comprises at least one of alumina, nano-silicon dioxide and boehmite; and / or, The material of the base film includes at least one of polyolefin, polyester and polyurethane.
3. The battery separator according to claim 1, characterized in that The insulating material includes ceramic powder, and the average particle size of the ceramic powder is 0.1 to 1 micron.
4. The battery separator according to claim 1, characterized in that The solid content of the natural latex is 10%-80%.
5. A method for preparing a battery separator according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing the binder with the insulating material to form a coating slurry; The coating slurry is coated on a base film and cured to prepare a battery separator.
6. The method for preparing a battery separator according to claim 5, characterized in that: The solid content of the coating slurry is 40-50%.
7. The method for preparing a battery separator according to claim 5, characterized in that: In the step of coating the coating slurry onto a base film and curing to obtain a battery separator, the coating thickness is 2 to 5 μm.
8. The method for preparing a battery separator according to claim 5, characterized in that: The steps of applying the coating slurry onto a base film and curing the coating slurry to prepare a battery separator include: The base film coated with the coating slurry is placed at a temperature of 40 to 45° C. and dried for 25 to 30 seconds.
9. A secondary battery, characterized in that: The secondary battery comprises the battery separator according to any one of claims 1 to 4 or a battery separator prepared by the method for preparing a battery separator according to any one of claims 5 to 8.
10. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 9.
Citation Information
Cited By
Battery monomer, battery device, energy storage device and power utilization device
CN121282473A